Efficacy and safety offerric citrate in treatment of hyperphosphatemia in patients with chronic kidney disease:a Meta-analysis - WANG Shan-shan; WEN Tong; ZHANG Xin-zhou (Linchuang shenzangbing zazhi)
Objective To evaluate the efficacy and safety of ferric citrate in treatment of hyperphosphatemia in patients with chronic kidney disease（CKD）,and provide evidence-based basis for clinical medication.Methods The literature on randomized controlled trials（RCTs） relating to treatment of hyperphosphatemia in patients with CKD was searched from the databases of Cochrane Library,PubMed,EMBase,and Web of Science.We used software RevMan5.3 to perform the Meta-analysis of the included RCTs to compare the efficacy and safety of ferric citrate versus placebo or other phosphorus binding agents in treatment of hyperphosphatemia in patients with CKD.Results A total of 1906 cases in 11 RCTs was included.Our meta-analysis showed that,compared to the control group,ferric citrate did better in alleviating hyperphosphatemia [MD=-0.66,95%CI（-0.77,-0.55）,P<0.01],where it reduced serum phosphorus compared with placebo [MD=-1.43,95%CI（-2.20,-0.66）,P<0.01] and was not inferior to other phosphorus binders [MD=0.10,95%CI（-0.11,0.30）,P=0.36].Furthermore,ferric citrate significantly improved hemoglobin,ferritin,transferrin saturation and hematocrit.In terms of adverse effects,compared with the placebo group or other phosphorus binder groups,in the ferric citrate group the incidence of diarrhea was higher and the incidence of constipation and bloating did not differ significantly between ferric citrate and placebo groups or other phosphorus binder groups.Conclusions Ferric citrate can effectively reduce serum phosphorus in patients with CKD and hyperphosphatemia,and also improve renal anemia.